2009
DOI: 10.1136/bmj.b183
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and access to care for South Asian Sikh and Muslim patients with life limiting illness in Scotland: prospective longitudinal qualitative study

Abstract: Objectives To examine the care experiences of South Asian Sikh and Muslim patients in Scotland with life limiting illness and their families and to understand the reasons for any difficulties with access to services and how these might be overcome. Design Prospective, longitudinal, qualitative design using in-depth interviews. Setting Central Scotland. Participants 25 purposively selected South Asian Sikh and Muslim patients, 18 family carers, and 20 key health professionals. Results 92 interviews took place. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
166
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(178 citation statements)
references
References 42 publications
(54 reference statements)
5
166
1
1
Order By: Relevance
“…They may also have difficulties in being understood by health and social workers, as well as understanding the service providers. A study assessing the vulnerability and access to care of South Asian patients in Scotland found that migrants with poor English language skills were less able to communicate their needs and negotiate care options (Worth et al 2009). Furthermore, many cultures have their own understanding of the aetiology of diseases.…”
Section: Access To Health and Social Services And Migrationmentioning
confidence: 99%
“…They may also have difficulties in being understood by health and social workers, as well as understanding the service providers. A study assessing the vulnerability and access to care of South Asian patients in Scotland found that migrants with poor English language skills were less able to communicate their needs and negotiate care options (Worth et al 2009). Furthermore, many cultures have their own understanding of the aetiology of diseases.…”
Section: Access To Health and Social Services And Migrationmentioning
confidence: 99%
“…The authors of the latter study argued that there is a need for a deeper qualitative understanding of the cultural and other factors that may facilitate or prevent home deaths. This is important since practitioners may struggle to provide culturally competent care if they do not appreciate the complexities underpinning patients and carers' concerns and preferences 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this include gatekeeping and low referral rates (Karim et al, 2000;Worth et al, 2009), differing patterns of disease, the restrictive referral criteria for hospices, communication issues (Richardson and Koffman, 2011), difficulty in accessing services, (Johnson, 2009) and poor satisfaction and mistrust of services (Frearson et al, 2013). Evidence suggests that actively involving BAME communities would help to raise awareness and increase access to services (Gunaratnum, 2006;Thacker and Faull, 2006).…”
Section: Introductionmentioning
confidence: 99%